Economic Investigation of Different Configurations of Inclined Solar Water Desalination Systems - Agboola, O. Phillips; Al-Mutaz, I. S.; Orfi, Jamel; Egelioglu, Fuat (Sage Publications Ltd, 2014)
This study empirically investigated the performance of four configurations of inclined solar water desalination (ISWD) system for parameters such as daily production, efficiency, system cost, and distilled water production cost. The empirical findings show that in terms of daily productivity improved inclined solar water desalination (IISWD) performed best with 6.41 kg/m(2)/day while improved inclined solar water desalination with wire mesh (IISWDWM) produced the least with 3.0 kg/m(2)/day. In terms of cost price of the systems, the control system inclined solar water desalination (ISWD) is the cheapest while IISWDWM is the most expensive system. Distilled water cost price ranges from 0.059 TL/kg, for IISWDW, to 0.134 TL/kg, for IISWDWM system. All the systems are economically and technically feasible as a solar desalination system for potable water in northern Cyprus. Potable water from vendors/hawkers ranges from 0.2 to 0.3 TL/kg.
Keywords: Single; Still; Performance; Humidification; Designs